Anticipating Peer Ranking Causes Hormonal Adaptations that Benefit Cognitive Performance - Carsten K. W. de Dreu; Klarita Gërxhani; Arthur Schram (Tinbergen Institute, 2019)
Performance ranking is common across a range of professional and recreational domains. Even when it has no economic consequences but does order people in terms of their social standing, anticipating such performance ranking may impact how people feel and perform. We examined this possibility by asking human subjects to execute a simple cognitive task while anticipating their performance being ranked by an outside evaluator. We measured baseline and post-performance levels of testosterone and cortisol. We find that (i) anticipating performance ranking reduces testosterone and increases cortisol; (ii) both these hormonal responses benefit cognitive performance; which explains why (iii) anticipation of being ranked by a peer increases cognitive performance.
Keywords: 330